1994
DOI: 10.1111/j.1399-6576.1994.tb03857.x
|View full text |Cite
|
Sign up to set email alerts
|

Poikilocapnic hypoxic ventilatory response in humans during 0.85 MAC isoflurane anesthesia

Abstract: Ventilatory responses to hypoxia (HVR) were investigated using poikilocapnic conditions (i.e. end-tidal CO2's allowed to seek it's own level) in 15 cardio-pulmonary healthy patients who were first studied awake and then at 0.85 MAC isoflurane. The influence of hypercapnia (HyperCapnic Ventilatory Response, HCVR) was also elucidated. Pneumotachography, capnography and airway occlusion pressures at 0.1 s (P degree 0.1) were used before and during both mild hypoxia (end-tidal O2 tension 8.7 kPa) and hypercapnia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…However, our results and those of Clergue and co-workers 12 suggest that peripheral chemoreceptors are not "silent" at anaesthetic concentrations of isoflurane and halothane, respectively, suggesting that although peripheral chemoreceptor responses are depressed, this is perhaps not to the degree as suggested by previous investigators. 3 Our findings also support recent studies by Lindahl's group [4][5][6] who found persistent ventilatory responses to hypoxia under poikilocapnic conditions in patients anaesthetized with 0.6-0.85 MAC of isoflurane and a reduction of 60-70% in HVR under isocapnic conditions with 0.85-1.1 MAC of isoflurane. Therefore, anaesthetic concentrations of isoflurane do not appear to suppress HVR to the same extent as that found by previous investigators.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, our results and those of Clergue and co-workers 12 suggest that peripheral chemoreceptors are not "silent" at anaesthetic concentrations of isoflurane and halothane, respectively, suggesting that although peripheral chemoreceptor responses are depressed, this is perhaps not to the degree as suggested by previous investigators. 3 Our findings also support recent studies by Lindahl's group [4][5][6] who found persistent ventilatory responses to hypoxia under poikilocapnic conditions in patients anaesthetized with 0.6-0.85 MAC of isoflurane and a reduction of 60-70% in HVR under isocapnic conditions with 0.85-1.1 MAC of isoflurane. Therefore, anaesthetic concentrations of isoflurane do not appear to suppress HVR to the same extent as that found by previous investigators.…”
Section: Discussionsupporting
confidence: 89%
“…However, recent studies have shown that HVR is not as sensitive to isoflurane and ventilatory response to hypoxia remained in patients anaesthetized with 0.6-1.1 MAC of isoflurane. [4][5][6] Animal studies also provide conflicting data as to whether or not HVR is depressed by volatile anaesthetics. 7 8 The site of action of volatile agents on HVR remains unclear.…”
mentioning
confidence: 99%
“…In other studies where end-tidal CO 2 was not artificially clamped to a constant value (poikilocapnia), 0.85 MAC isoflurane did not significantly depress HVR probably because of the interaction between the central and peripheral ventilatory control mechanisms [92,93]. HCVR is much larger than HVR under most conditions, and so when CO 2 is allowed to rise, the stimulation of ventilation by HCVR may simply render anesthetic depressant effects upon HVR inconsequential.…”
Section: Inhalational Anestheticsmentioning
confidence: 99%